2022
DOI: 10.3390/ijerph19073977
|View full text |Cite
|
Sign up to set email alerts
|

Various Aspects Involved in the Study of Tooth Bleaching Procedure: A Questionnaire–Based Study

Abstract: A beautiful smile is an important feature when it comes to a pleasant appearance of the face, and one of the most common situations that drive patients to book a dental appointment is tooth discoloration. Tooth bleaching is the treatment of choice for extrinsic tooth discoloration, as it is a cheap, fast, and minimally invasive procedure. This study aimed to provide comparative information on the perceptions of both patients and dentists regarding different whitening methods and on the factors involved in peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…26 Interestingly, a questionnaire indicated that participants tended to express greater satisfaction with in-office bleaching results, whereas dentists favored at-home bleaching. 27 Another study similarly reported high satisfaction levels with bleaching treatments. 29 However, there was only a weak correlation observed between the degree of tooth color change and patient satisfaction.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…26 Interestingly, a questionnaire indicated that participants tended to express greater satisfaction with in-office bleaching results, whereas dentists favored at-home bleaching. 27 Another study similarly reported high satisfaction levels with bleaching treatments. 29 However, there was only a weak correlation observed between the degree of tooth color change and patient satisfaction.…”
Section: Introductionmentioning
confidence: 97%
“…[19][20][21][22][23][24] Additionally, participants' satisfaction with bleaching treatments is significantly influenced by factors, including the degree of color change, treatment methodology, treatment duration, and auxiliary aids. [25][26][27] Understanding the interplay between patient satisfaction and tooth color change is crucial for devising appropriate and tailored treatment plans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmetic procedures, such as tooth bleaching, have increased patients' self‐confidence and improved emotional well‐being, 1 making the procedure increasingly popular 2,3 . In a recent study, it was observed that 86% of the participants underwent the bleaching technique on their initiative and not at the dentist's suggestion 4 …”
Section: Introductionmentioning
confidence: 99%
“…These treatments can change the color of discolored teeth such that they become bright. Due to globalization and the growing modernization of all sectors, both men and women have developed heightened aesthetic sensibilities and place a premium on any aspect of their look that would improve their appearance, including smiling brightly and whitely [11][12][13][14]. Because tooth whitening is an affordable, quick, and minimally invasive process, it is now the treatment of choice for tooth staining among all available alternatives for treating tooth discoloration [11,12].…”
Section: Introductionmentioning
confidence: 99%